Development of Core‐Shell Nanoparticle Drug Delivery Systems Based on Biomimetic Mineralization. (8th June 2020) - Yang, Guangze; Liu, Yun; Jin, Song; Zhao, Chun‐Xia
Abstract: Among various drug‐delivery systems, core‐shell nanoparticles have many advantages. Inspired by nature, biomimetic synthesis has emerged as a new strategy for making core‐shell nanoparticles in recent years. Biomimetic mineralization is the process by which living organisms produce minerals based on biomolecule templating that leads to the formation of hierarchically structured organic–inorganic materials. In this minireview, we mainly focus on the synthesis of core‐shell nanoparticle drug‐delivery systems by biomimetic mineralization. We review various biomimetic mineralization methods for fabricating core‐shell nanoparticles including silica‐based, calcium‐based and other nanoparticles, and their applications in drug delivery. We also summarize strategies for drug loading in the biomolecule‐mineralized core‐shell NPs. Current challenges and future directions are also discussed. Abstract : Under the right conditions : Bio‐inspired core‐shell NPs offer various opportunities in drug delivery, imaging and sensing applications. In contrast to conventional methods for fabricating core‐shell NPs, biomimetic synthesis occurs under physiological conditions, resulting in sustainable, facile manufacture and enhanced biocompatibility.